Use of Cratylia argentea in the tropical zone of Colombia (Revista Sistemas de Producción Agroecológicos, 2015)
Feeding dairy cows in dual purpose systems in the eastern plains of Colombia, it is mainly based on Brachiaria pastures, which are in different stages of degradation. A limitation in both rainy and drought is the low protein content in the forage which determines the low production of milk and need to supplement during the dry season to concentrate if we want to maintain production therefore biological efficiency and economic of these systems is low, which negatively affects revenues and competitiveness of producers of meat and milk. To help improve food resources in small dairy farms, it has carried out several projects to validate and promote the use of Cratylia (veranera). In a first project 14 farms were selected whose main activity was the production of milk, with the active participation of producers 11.8 ha were established, of which 6.5 were designed to cut and carry, 3 for browsing and 2.26 for seed production. In parallel, we work Cratylia use the "Research Center La Libertad" were performed; Acacias penal colony also was established 2 ha in the Santana farm in the flat altillanura, 20 has in eight agricultural schools in the region and several batches of seed production destined to the promotion of bougainvillea between producers. Hence the exercise of the creation of the National Network Cratylia Producers, which had its trials in different agro-ecological zones of the country was conducted. Both on farms and in schools, the producers supplied the labor required for the establishment and maintenance of crops. In the rainy season Cratylia production on farms it was on average 3.34 ton/ha of dry matter (DM) with 66% leaf and plant height of 137 cm. During the dry season production was 0.59 ton/ha of DM with 52% leaf and a height of 112 cm. The crude protein content (PC) of Cratylia during the dry season averaged 21.67%, while the companion grass was 6.52%. Yields of clean seeds in batches established in seven farms were lower than initially expected; in the first dry season there were only 33 kg/ha, equivalent to 47 g/plant, being significantly lower than the yields obtained in Costa Rica with the same legume. The results have shown that it is an excellent alternative for increasing productivity in the Eastern Plains and allows to increase meat production per hectare per year, compared with the traditional system of pasture alone.
Keywords: shrubby forage; supplementation; legume; feeding